Modelling for crop response to water: phisiological aspects - Steduto P. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
The issue of crop response to water is presented in a theoretical framework which highlights some of the main approaches developed over time. After a brief introduction dealing with the advantages of using modelling as a quantitative tool in serving agricultural science, various physiological processes are synthetically reviewed in terms of their response to water stress. This introduces the basis for conceptual modelling of crop growth with notable focus on response to water. The standing crops are thus considered as dependent on their capture and use of environmental resources such as solar radiation, carbon dioxide, water and nutrients, and their growth and productivity are formulated both in terms of empirical and mechanistic relations. The approaches of solar-radiation and transpiration as related to productivity are discussed. However, all crop models generally allow the construction of a 'production function' of crop yield versus water use, which is necessary for the economic evaluation of water management at farm and regional scale. The specific case of the crop-growth submodel of EPIC (Erosion Productivity Impact Calculator) is reported as a relatively simple example of implementation of processes integration to mechanistically simulate growth and productivity. While discussing distinctive features of crops models relative to crop-water relations, limits in their use in the Mediterranean Basin are highlighted. Specifically, modelling aspects on tree crops and salinity are recalled. Relatively extensive literature is reported to allow further insight on the various subjects treated. Finally, words of caution, perspectives, and research needs concerning crop models are remarked in the conclusions
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)